F-root square mean labeling of line graph of some graphs - Arockiaraj S.; Baskar, A. Durai; Kannan, A. Rajesh (Utilitas Mathematica, 2019)
A function f is called a F-Root Square Mean labeling of a graph G(V,E) withp vertices and q edges if f: V(G) → {1,2,3,...,q + 1} is injective and the induced function f∗defined as f∗(uv) — [√f(u)2+f(v)2/2 for all uv ∈ E(G), is bijective. A graph that admits a F-Root Square Mean labeling is called a F-Root Square Mean graph. The line graph is one among the graph operations. In this paper, it is tried to analyse that the line graph operation preserves the F-Root Square Mean property. Here we have discussed the F-Root Square Meanness of line graph of the path, cycle, star, Pn°S1, PnoS2, [Pn; S1], S(PnoS1), ladder, slanting ladder, the crown graph Cno S1and the arbitrary subdivision of S3. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.